CONVERGENCE OF GAUSS CONTINUED FRACTION FOR THE RATIO OF HYPERGEOMETRIC FUNCTIONS IN Qp - Симотюк, Михайло Михайлович; Медвідь, Оксана Мирославівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The conditions of convergence of Gauss continued fraction to the ratio of hypergeometric functions in the field of p-adic numbers are established.